SISTEM PESAWAT TANPA AWAK MENGGUNAKAN KAMERA THERMAL UNTUK MEMBANTU PENCARIAN KORBAN BENCANA ALAM - Feryanda Frasiska, I Gede; Budiastra, MKes., MT, Ir. I Nyoman; Rahardjo, S.T.,M.T., Pratolo (Jurnal SPEKTRUM, 2020)
In Indonesia, the weather is influenced by seasons, namely the dry season and the rainy season. Apart from weather, natural disasters can also occur due to the earth's tectonic patterns, either in the form of tsunamis or earthquakes. Every natural disaster will have a detrimental impact on society both economically and socially. The impact of a disaster like an earthquake is the collapse of buildings. Collapsed buildings due to earthquakes can leave large numbers of people dead or buried in the rubble. The evacuation process of post-disaster victims must be carried out immediately to reduce the risks posed by the disaster, such as the number of casualties caused by delays in the evacuation process. Based on these problems, researchers are motivated to create a technological innovation that can help the SAR team iin the processs of detecting victims from debris through the air by detecting the victims body temperature, the number of victims and showing the coordinates of the victim's position. disaster victims. The tool is called DROPBA, which is an Unmanned Aircraft System or UAV that uses thermal cameras to help search for victims of natural disasters. The SAR team at the post will control DROPBA or Unmanned Aircraft to detect disaster victims who are in the wreck, and inform the SAR team information wirelessly in the form of a path to the position of the disaster victim. The design results are in the form of a 3-dimensional model image from the                                                                                                              DROBA tool and the components and camera systems used are a thermal camera connected to the Raspberi pi system and image processing using Open CV.